2008
DOI: 10.1111/j.1747-0080.2007.00178.x
|View full text |Cite
|
Sign up to set email alerts
|

Meal and food preferences of nutritionally at‐risk inpatients admitted to two Australian tertiary teaching hospitals

Abstract: Aim:  To determine preferences for meals and snack of long‐stay patients and hospitalised patients with increased energy and protein requirements. Methods:  Using consistent methodology across two tertiary teaching hospitals, a convenience sample of adult public hospital inpatients with increased energy and protein requirements or longer stays (seven days or more) were interviewed regarding meal and snack preferences. Descriptive reporting of sample representativeness, preferred foods and frequency of meals an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
0
11
0
1
Order By: Relevance
“…Improved packaging had a feasibility of 2.5, suggesting it might be relatively easy to address. Forty‐nine percent of patients surveyed in two Queensland teaching hospitals had difficulty opening packaging 7 and this problem was identified also in our previous study 23 . The use of packaged items appears to be increasing, which can adversely affect the visual appeal of the meal, the environment and negatively impact food consumption.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Improved packaging had a feasibility of 2.5, suggesting it might be relatively easy to address. Forty‐nine percent of patients surveyed in two Queensland teaching hospitals had difficulty opening packaging 7 and this problem was identified also in our previous study 23 . The use of packaged items appears to be increasing, which can adversely affect the visual appeal of the meal, the environment and negatively impact food consumption.…”
Section: Discussionmentioning
confidence: 57%
“…The prevalence of malnutrition in Australian hospitals has been reported to be up to 49%. [1][2][3][4][5][6][7] There are many possible causes and long-stay and elderly patients are particularly vulnerable. [7][8][9][10][11] Malnutrition in the hospitalised elderly is preventable and treatable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(23) In addition, patient eating patterns and meal preferences can change over the period of their hospitalisation, such as a preference for smaller more frequent meals. (24) This study has demonstrated that patient engagement through HIT has created an opportunity to increase dietary intake, and may be a valuable strategy to enhance feelings of engagement and consequently the appetite of patients. The NA can offer an important link between the patient and their meal, and assist patients to make suitable menu choices to meet their requirements and food and meal pattern preferences.…”
Section: Discussionmentioning
confidence: 85%
“…Researchers have estimated that 40% of UK hospital patients are malnourished, and further studies have shown that older patients are five times more likely to be at risk of malnutrition than younger patients …”
Section: Introductionmentioning
confidence: 99%